2005
DOI: 10.1111/j.1708-8208.2005.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Follow-Up Study of Titanium Dioxide–Blasted Implants

Abstract: This study showed that titanium dioxide-blasted implants offer predictable long-term results as supports for fixed prostheses in both the maxilla and mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
141
5
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(172 citation statements)
references
References 18 publications
(36 reference statements)
25
141
5
1
Order By: Relevance
“…There is no reliable information about other surface micro-factors being important for osseointegration -the order of irregularities seems irrelevant (anisotropy or isotropy; Gö ranson et al, 10 ); the precise way to manufacture irregularities seems irrelevant (each company seems to prefer their own method) and good clinical results have been reported for many modern implant systems. [11][12][13][14][15] There is a substantial problem in evaluating effects of changing the nano-topography of an implant; if surface changes are performed at the nanometer resolution level, there will be simultaneous alterations of the micro-roughness, hence it is difficult to evaluate …”
Section: The Effect Of Implant Surface Irregularities At the Micrometmentioning
confidence: 99%
“…There is no reliable information about other surface micro-factors being important for osseointegration -the order of irregularities seems irrelevant (anisotropy or isotropy; Gö ranson et al, 10 ); the precise way to manufacture irregularities seems irrelevant (each company seems to prefer their own method) and good clinical results have been reported for many modern implant systems. [11][12][13][14][15] There is a substantial problem in evaluating effects of changing the nano-topography of an implant; if surface changes are performed at the nanometer resolution level, there will be simultaneous alterations of the micro-roughness, hence it is difficult to evaluate …”
Section: The Effect Of Implant Surface Irregularities At the Micrometmentioning
confidence: 99%
“…The realization that implants made of commercially pure titanium attain direct bone to implant contact initiated this revolution in oral rehabilitation. This phenomenon of osseointegration (or functional ankylosis) was first described by Brå nemark et al 1 and Schroeder et al 2 There have been numerous studies published evaluating clinical outcomes of implants placed in institutional settings, [3][4][5][6][7][8][9] but there are few references relating to implants placed and restored in private practice settings. [10][11][12] The aim of this retrospective study was to analyse the clinical parameters involved in the planning, placement, survival and success of 1000 consecutively placed Straumann (formerly ITI) implants in a private specialist periodontal practice.…”
Section: Introductionmentioning
confidence: 99%
“…Other experimental studies confirmed the increase in BIC for titanium grit-blasted surfaces 12,29 . Other studies have reported high clinical success rates for titanium grit-blasted implants, up to 10 years after implantation 30,31 . Comparative clinical studies gave higher marginal bone levels and survival rates for TiO2 grit-blasted implants than for machined turned implants 32,33 .…”
Section: Roughening Of Implants By Grit-blastingmentioning
confidence: 94%